EMPLOYEE WORK TARGETS (SKP) INFORMATION SYSTEM AND WEB-BASED EMPLOYEE PERFORMANCE ASSESSMENT DESIGN - Hasibuan, Yuda Mahendra (Bina Bangsa International Journal of Business and Management, 2024)
Determined in the SKP Employee Work Targets are what will be provided by a single employee of a Civil State. Employee targets contain job duties activities and targets that must be completed in sufficient and flexible time (PP 46, 2011). PERKA BKN No. 01 TAHUN 2013 and PP No. 46 TAHUN 2011 are the basic documents for employee work targets. The only thing the most important thing to understand about the work a caregiver is doing at any given time is the job title. At Surabaya State University, employee performance assessments are mainly carried out through semi-manual procedures or by manually entering data into a predetermined format.